Potensi Sirih Gading (Epipremnum aureum) dan Lili Paris (Chlorophytum comosum) Sebagai Sarana Fitoremediasi PM2.5 di Dalam Ruangan - Didar Haq, Abiyyu; Rahim, Aulia Riezka; Rahayu, Luh Ade Dita (Faculty of Medicine Universitas Mataram, 2021)
92% of world population breathe dirty air because of high concentration of air pollutant. Air pollutant contributed in 43% of all Chronic Obstructive Pulmonary Disease (COPD). Particulate Matter 2.5 (PM2.5), the most dangerous component of air pollutant, has caused 4,2 million death in 2017. PM2.5 is classified into indoor PM2.5 and outdoor PM2.5. Outdoor PM2.5 has a higher average concentration than indoor PM2.5 therefore it is possible that outdoor PM2.5 influence the indoor PM2.5. Remediation is an effort to restore the air from any pollutant. Remediation technique that often used is using chemical to absorp, filtrate, ozonise, and photolyse. Phytoremediation is a remediation that utilize the surface characteristic of plants part and microorganism in the plant phyllosphere. Sirih gading (Epipremnum aureum) and lili paris (Chlorophytum comosum) has been proven to have a surface characteristic that are very effective in accumulating PM2.5. Beside that, microorganism in both of the plant’s phyllosphere are known to be able to detoxify PM2.5. Microorganism that have the ability to detoxify PM2.5 in Epipremnum aureum’s phyllosphere is Aspergillus niger, Aspergillus fumigatus, and Firmicutes bacteria. In other hands, microorganism in Chlorophytum comosum that has that ability to detoxify is Proteobacteria phyla.